A Question of Morality: Sorcery and Concepts of Deviance among the Kabana, West New Britain - McPherson, Naomi M. (Anthropologica, 2022)
For the Kabana of New Britain, deviant behaviour is essentially the advancement of self-interest untempered by self-regulation such that the individual infringes on the ability of others to pursue their own self-interest. Social labelling is applied to deviant behaviours, but no permanent stigma attaches to individuals. Reactions to deviance include shame, gossip and ridicule, proceedings before the village magistrate and sorcery. The performance of sorcery, a major cause of death, is a complex and ambiguous event, insofar as a sorcerer’s threat may both inhibit deviance and mediate conflict, but the actual enactment of the threat is itself a deviant act. In cases where a victim’s illness is attributed to sorcery, a moot may be held to discern the motives of sorcery and identify the sorcerer. In a particular case, which is examined at length here, failure clearly to identify the sorcerer was followed by the victim’s death.